An Analysis of the Connotative Meanings in NIKI’s “Anaheim” Song Lyrics - Andra, Meidi; Handayani, Nurma Dhona (Universitas Muhammadiyah Barru, 2026)
Addressing a gap in cross-cultural semantic studies of Indonesian global artists, this paper investigates the connotative meanings embedded in NIKI’s “Anaheim” lyrics. The study employs a descriptive qualitative research design to interpret the connotative meanings conveyed through linguistic choices in NIKI’s lyrics. The study employs document and content analysis of the song’s written text. Ten lyrical excerpts were systematically read, annotated, and coded to identify recurring lexical items, metaphors, and thematic patterns. The coding process, validated through peer discussion and reference triangulation, ensured interpretive reliability and analytical depth. Drawing on Leech’s semantic framework and supported by transnational identity theory, the analysis highlights how “Anaheim” constructs themes of loss, emotional transformation, and cultural hybridity. The findings reveal that NIKI’s nuanced use of connotative language transforms personal experience into a universal emotional narrative, illustrating how linguistic creativity serves as a medium of identity negotiation within the global pop music landscape